resevol: An R package for spatially explicit models of pesticide resistance given evolving pest genomes - Duthie, A. Bradley; Mangan, Rosie; McKeon, C. Rose; Tinsley, Matthew C.; Bussière, Luc F. (PLoS computational biology, 2023)
The evolution of pesticide resistance is a widespread problem with potentially severe consequences for global food security. We introduce the resevol R package, which simulates individual-based models of pests with evolving genomes that produce complex, polygenic, and covarying traits affecting pest life history and pesticide resistance. Simulations are modelled on a spatially-explicit and highly customisable landscape in which crop and pesticide application and rotation can vary, making the package a highly flexible tool for both general and tactical models of pest management and resistance evolution. We present the key features of the resevol package and demonstrate its use for a simple example simulating pests with two covarying traits. The resevol R package is open source under GNU Public License. All source code and documentation are available on GitHub.